2022
DOI: 10.3389/fimmu.2022.891698
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures Reveal Common Virus Infection Pathways in Target Tissues of Type 1 Diabetes, Hashimoto’s Thyroiditis, and Celiac Disease

Abstract: Type 1 diabetes (T1D) patients are at heightened risk for other autoimmune disorders, particularly Hashimoto’s thyroiditis (HT) and celiac disease (CD). Recent evidence suggests that target tissues of autoimmune diseases engage in a harmful dialogue with the immune system. However, it is unclear whether shared mechanisms drive similar molecular signatures at the target tissues among T1D, HT, and CD. In our current study, microarray datasets were obtained and mined to identify gene signatures from disease-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We can notice other potential viruses: retrovirus [88], human polyomavirus 2, Enterobacteria phage mEpX1, and Enterobacteria phage mEpX2 [89]. A study based on gene signatures revealed a possible between several autoimmune diseases, including CD and several other viruses: influenza A, human T-lymphotropic virus type 1, and herpes simplex infection [90]. Rubella may be protective: sera of anti-rubella IgG were higher in the control group (87.8% vs 94.9%) and may demonstrate a possible protective role against CD in a study on 297 healthy subjects and 90 patients [27].…”
Section: Others Virusmentioning
confidence: 99%
“…We can notice other potential viruses: retrovirus [88], human polyomavirus 2, Enterobacteria phage mEpX1, and Enterobacteria phage mEpX2 [89]. A study based on gene signatures revealed a possible between several autoimmune diseases, including CD and several other viruses: influenza A, human T-lymphotropic virus type 1, and herpes simplex infection [90]. Rubella may be protective: sera of anti-rubella IgG were higher in the control group (87.8% vs 94.9%) and may demonstrate a possible protective role against CD in a study on 297 healthy subjects and 90 patients [27].…”
Section: Others Virusmentioning
confidence: 99%
“…The genetic contribution to islet inflammation pathways is apparent in T1D, with polymorphisms in the interferon system (41,42) and interferon and viral infection signatures identified in islets of organ donors with T1D (43,44). Even in T2D, where gene mutations are related to glucose homeostasis in b cells and insulin target tissues (45), genetic variants affecting viral response pathways have been identified; for example, a TYK2 promoter variant associated with a deteriorated cytokine response has been identified as risk factor for T1D as well as T2D (46) and correlates with increased T2D severity (47).…”
Section: Introductionmentioning
confidence: 99%